Flexible Work Arrangements and Precautionary Behavior: Theory and Experimental Evidence - Andreas Orland; Davud Rostam-Afschar (Global Labor Organization (GLO), 2020)
In the past years, work time in many industries has become increasingly flexible opening up a new channel for intertemporal substitution. To study this, we set up a two-period model with wage uncertainty. This extends the standard savings model by allowing a worker to allocate a fixed time budget between two work-shifts or to save. To test the existence of these channels, we conduct laboratory consumption/saving experiments. A novel feature of our experiments is that we tie them to a real-effort style task. In four treatments, we turn on and off the two channels for consumption smoothing: saving and time allocation. Our four main findings are: (i) subjects exercise more effort under certainty than under risk; (ii) savings are strictly positive for at least 85 percent of subjects (iii) a majority of subjects uses time allocation to smooth consumption; (iv) saving and time shifting are substitutes, though not perfect substitutes.
Keywords: D14; E21; J22; C91; D81; 330; precautionary saving; labor supply; intertemporal substitution; experiment